Association between the number of natural teeth and diabetic retinopathy among type 2 diabetes mellitus: The Korea national health and nutrition examination survey. Issue 47 (November 2017) - Song, Su Jeong; Han, Kyungdo; Lee, Seong-su; Park, Jun-Beom
Abstract : Abstract: The aim of this study was to investigate the relationship between the number of teeth and diabetic retinopathy among Korean population. This was a retrospective analysis using data of total 45, 811 individuals who participated in the Korea National Health and Nutrition Examination Survey (KNHANES) 2008 to 2012. Among these, 2593 (5.7%) participants were identified as having type 2 diabetes mellitus. After excluding participants without ophthalmic evaluation or other variables, 2078 (80%) participants were included. Demographic factors including dental status were analyzed and compared between participants with and without diabetic retinopathy. Among the 2078 type 2 diabetes, 358 (17.2%) had diabetic retinopathy. Type 2 diabetes with fewer teeth were more likely to have diabetic retinopathy ( P   <  .001). Multivariate analysis showed that type 2 diabetes with < 20 teeth had an 8.7-fold risk of having vision-threatening diabetic retinopathy when compared with type 2 diabetes with ≥28 teeth (95% confidence interval: 2.69–28.3) after adjusting for age, sex, body mass index, smoking, drinking, exercise, hypertension, diabetes mellitus duration, and glycated hemoglobin level. The number of teeth was found to be an independent risk factor for diabetic retinopathy. Thus, a comprehensive approach of dentists and ophthalmologists is needed to minimize the complications of diabetes mellitus. Whether the teeth number reflects microvascular changes of the retina among type 2 diabetes warrants further investigation.